Ekspresi Programmed Death Ligand-1 (PD-L1) pada Seminoma Testis sebagai Potensi Faktor Prognostik - Freciyana Boedijono; Budiana Tanurahardja; Ria Kodariah (Majalah Patologi Indonesia, 2020)
BackgroundThe prognosis of testicular seminoma cases which failed to be cured with conventional therapy is poor. Several recurrent eventsafter chemotherapy were also found. PD-L1 is expressed in various types of malignancy and tumor infiltrating lymphocytes (TILs)and its role is known as a prognostic factor. This study was conducted to determine the role of PD-L1 expression seminoma indetermining overall survival (OS) and progression free survival (PFS).MethodsThis is a retrospective cohort study with survival analysis. Clinical data were obtained from medical record in RSUPN CiptoMangunkusumo since January 2011-December 2016 and observed for 2 years. Histopathological data were obtained fromAnatomical Pathology Department and PD-L1 immunohistochemical staining were performed.ResultsA significant correlation between PD-L1 expression in tumor cells with 2-year OS (p=0.023) and PFS (p=0.002) in testicularseminoma was found. No significant correlation between PD-L1 expression in TILs with 2-year OS (p=0.235) and PFS (p=0.111).We also found significant correlations between PD-L1 expression of tumor cells and TILs with PFS (p=0.019). A significantcorrelation between stage with 2-year OS (p=0.010) and PFS (p=0.000) and lymph node metastases with 2-year OS (p=0.010) andPFS (p=0.000).ConclusionPD-L1 expression of testicular seminoma cells were significantly correlated with OS and PFS. There were no statistically significantassociations between PD-L1 expression in TILs with OS and PFS.